Pengaruh Defisit Pendanaan Internal Terhadap Struktur Modal - Andik Susanto; Novy Rachma Herawati (Universitas Merdeka Madiun, 2020)
CompaniesÂ manage its capital structure in order to provide benefits to the company so as to encourage management to manage the capital structure so that the composition of debt or equity can be adjusted with the aim of management in selecting the composition. This research focuses on the pecking order theory by taking a sample of 33 property, real estate, and building construction companies listed on the Indonesia Stock Exchange with the observation year 2015 to 2017. The purpose of this study is to see if there is consistency of research, as well as the previous studies to answer the research gap of extended pecking order theory model to see the effects of internal funding deficit and the debt ratio to the addition of forming internal funding deficit (dividends payment, additional working capital, investment and net cash flow) for additional debt ratio that can be used as a factor affecting changes in capital structure. The final results in this study support the hypothesis that the entire internal funding deficit has a positive effect on additional debt ratio. Dividend payments, additional working capital, net cash flow, and investment have a positive effect. So the company can be said to support the pecking order theory.Â Keywordsâ€”: capital structure; pecking order theory; internal funding deficit; dividend payments; additional working capital.